Comparison of feed consumption of pigs in two lines - J D Wheat; Donald H Kropf; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1976)
Pigs in the control line ate more, grew faster, and were less efficient than those in the select line.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Control vs. select line